Modulated Synthesis of Self‐Standing Covalent Organic Framework Films - Wang, Yang; Guo, Bei; Yang, Tong; Zhang, Zhi‐Cong; Liang, Lin; Ding, San‐Yuan; Wang, Wei (Chemistry : a European journal, 2022)
The weak interaction of covalent organic framework (COF) nanoparticles makes the preparation of self‐standing COF films difficult. Herein, a modulated strategy for the facile synthesis of self‐standing COF films with good crystallinity and tunable thickness is reported. As compared with the non‐modulated approach, the modulated strategy changes the COF morphology from nanoparticles to nanofibers, enabling the facile preparation of self‐standing COF films with improved mechanical properties. The Young's modulus of the self‐standing COF film obtained via the modulated strategy could increase by 26 times. Moreover, self‐standing LZU‐8 film can be used as a membrane for efficient removal of 99 % mercury ions from aqueous solution. Our results open up a new approach to prepare self‐standing COF thin films for practical applications. A modulated strategy was developed for the synthesis of self‐standing COF films with good crystallinity and tunable thickness. As compared with the non‐modulated method, the modulated approach changes the COF morphology from nanoparticles to nanofibers, enabling the facile preparation of self‐standing COF films with improved mechanical properties. The Young's modulus of the self‐standing COF film obtained via the modulated strategy could increase by 26 times.